Risk factors in the development of intraventricular haemorrhage in the preterm neonate. Issue 6 (June 1982) - Levene, M I; Fawer, C L; Lamont, R F
Abstract : One hundred and forty-six infants of 34 weeks' gestation or less were repeatedly scanned by means of real-time ultrasound to diagnose the presence of intraventricular haemorrhage (IVH), its severity, and the timing of onset of the condition. We describe a new method for grading the extent of the IVH which does not depend on ventricular size. IVH was clearly present in 52 (36%) of the 146 infants and in 32 (50%) of the 64 infants of 30 weeks' gestation or less. Repeated scans accurately timed the onset of IVH in 41 infants, and 32 (78%) had the first sign of IVH before 72 hours of age. Thirty-two clinical factors were analysed for possible correlation with the development of IVH: outborn compared with inborn, administration of sodium bicarbonate, hypothermia, intermittent positive pressure ventilation, continuous positive airways pressure, hypercapnia, severe acidosis, and respiratory distress syndrome all reached statistical significance. Analysis of variance showed that respiratory distress syndrome was the most important factor, but severe acidosis had some independent action on the development of IVH. Seventeen (81%) of 21 infants with hypercapnia (PCO2 greater than 6 kPa) together with severe acidosis (pH less than 7.1) developed IVH, of which more than half was moderate or severe in degree.